Sand-nonwoven geotextile interfaces shear strength by direct shear and simple shear tests - Castorina Silva Vieira (2015)
Soil-reinforcement interaction mechanism is an important issue in the design of geosynthetic reinforced soil structures. This mechanism depends on the soil properties, reinforcement characteristics and interaction between these two elements (soil and reinforcement). In this work the shear strength of sand/geotextile interfaces were characterized through direct and simple shear tests. The direct shear tests were performed on a conventional direct shear device and on a large scale direct shear apparatus. Unreinforced sand and one layer reinforced sand specimens were characterized trough simple shear tests. The interfaces shear strength achieved with the large scale direct shear device were slightly larger than those obtained with the conventional direct shear apparatus. Notwithstanding the differences between the shear strength characterization through simple shear and direct shear tests, it was concluded that the shear strength of one layer reinforced sand is similar to the sand/geotextile interface direct shear strength. (c) 2015 Techno-Press, Ltd.